Recent Bank Support for Civil Service Reconstruction in Post-Conflict Countries - Mukherjee, Ranjana (World Bank, Washington, DC, 2012)
Civil service reconstruction is important in post-conflict countries because conflict erodes institutions and civil service capacity. And because successful reconstruction-in all sectors -requires domestic capacity to implement projects, a weak civil service undermines overall reconstruction efforts. Moreover, donor assistance is crucial to a country's rebuilding, and coordinating such assistance requires a certain amount of civil service capacity. In addition, the Bank has found that country ownership is essential for successful projects. But country ownership can be jeopardized if international agencies and nongovernmental organizations (NGOs) dominate reconstruction efforts, overwhelming states already weakened by conflict. Civil service reconstruction offers an opportunity to start anew, with little of the resistance to civil service reform often encountered from politicians and civil servants. It allows good practices to be instilled from the outset-without having to undo bad ones.